Identifying Characteristics of Coffee Beans Using the Case Based Reasoning Method - Lazary Siahaan, Kharis Bobo; Yusman, Yanti; Lesmana Siahaan, Muhammad Donni (Cattleya Darmaya Fortuna, 2024)
Using Case-Based Reasoning (CBR) method as an approach to identify the characteristics of coffee beans. CBR is a method that uses knowledge from past cases to solve new problems by finding similar cases based on them and applying the same solution. This database is used to match existing coffee bean standards with future identified coffee bean characteristics. Two types of coffee beans, Arabica and Robusta, are used as case studies to identify new coffee beans. A program will be developed to implement the system using Matlab application as the system design. Arabica coffee bean varieties were found to be the most similar with a value of 0.66% for case A. The calculation result of case B shows that the most similar Robusta coffee bean variety has a similarity of 1%. The identification results have their own coffee bean variety suitability values for each case. As a result, the program created allows even laypeople to easily identify the type of coffee beans.